Association of CYP2C19*2 polymorphisms and high on-treatment platelet reactivity in acute myocardial infarction or coronary artery in-stent restenosis patients during dual antiplatelet therapy - Yawei Yang; Wei Zhang; Pan Li; Ying Gu; Liping Ma; Min Fan (Elsevier, 2020)
Objective: Cytochrome CYP2C19 mutant allele is associated with high on-treatment platelet reactivity (HTPR) after standard clopidogrel treatment, which is accompanied by an increased risk of ischemic events. This study assesses the association of CYP2C19 mutant allele with HTRR and its response to antiplatelet therapy in acute myocardial infarction (AMI) or coronary artery in-stent restenosis (ISR). Methods: CYP2C19 (*2, *3, *17) and ABCB1 genotyping were performed in a series of 98 AMI or ISR patients treated with standard-dose clopidogrel (75 mg, term daily). Platelet activity was measured by VerifyNow assay, with HTPR defined as P2Y12 reaction units (PRUs) >208. The patients with HTPR (n = 48) were randomly assigned to receive either high-dose clopidogrel (150 mg, term daily; n = 24) or ticagrelor (90 mg, bid; n = 24). Results: No association was observed between CYP2C19*3, ABCB1 genotype and platelet reactivity (PR) (P > .05 for all). A significantly higher frequency of HTPR were observed in the patients carrying CYP2C19*2 homozygotes (n = 9; 9/11, 81.8%) than the CYP2C19*2 allele carriers (n = 26; 26/48, 54.2%, P < .05) and the non-carriers (n = 13; 13/39, 33.3%, P < .001). No patient exhibited HTPR after treatment with ticagrelor irrespective of CYP2C19 genotype, whereas 5 (100%) patients with CYP2C19*2 homozygotes, 7 (50%) CYP2C19*2 allele carriers and 3 (60%) non-carriers after high-dose clopidogrel remained HTPR (P < .05 for all). Conclusion: A higher rate of HTPR was observed in AMI or ISR patients with CYP2C19*2 homozygotes than those with one or none allele. In patients carrying CYP2C19*2 homozygotes, ticagrelor is significantly more effective in reducing platelet reactivity than high-dose clopidogrel.